PEMBELAJARAN APRESIASI CERPEN SISWA KELAS XI SMA YAYASAN PEMBINA UNIVERSITAS LAMPUNG BANDAR LAMPUNG TAHUN PELAJARAN 2012/2013 - yenni indriani; ni nyoman wetty suliani; siti samhati (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
The problem has been discussed in this research is students’ short stories appreciation learning at second grade of SMA YP Unila Bandar Lampung year 2012/2013. The objective of this research is to describe learning as planning activation, and scoring process. The method used in this research is descriptive method. Data source in this research is Lesson Planning (RPP), the learning process (teachers’ activity in teaching and students’ activity in learning), and scoring. The result shows that lesson planning that has been designed by teacher is based on standard of Lesson Plan. The teaching process is a teacher’s activity in teaching and students’ activity in learning. Teacher’s skill in explaining the using of learning media, strategy/ method used by the teacher is based on SK/KD of indicator and learning objective. Students’ learning activities are including oral activity, written activity, listening activity, mental activity and emotional activity in short story appreciation learning. The teacher scores the students’ result in appreciating short stories by using Test technique. Based on the result of this research, it can be concluded that students’ short stories appreciation learning at second grade of SMA YP Unila Bandar Lampung year 2012/2013 are lesson planning process, learning activation, and scoring/ learning evaluation.Keywords: activation, learning, planning, scoring